Literature of Green Architecture - Vikas Bhola (International Journal of Urban Design and Development, 2024)
The term green architecture implies the use of environmental principles as the basis when designing buildings. In this perspective, the architecture of the future aims at synthesizing nature, technology, science, and even the imagination in the construction industry. The following paper explores green architecture on a generalized basis, which discusses its basic features, practices and the repercussions of green design on environmental sustainability. A key component of eco-architecture is to make sure that the use of resources are reduced, the environmental impact is curtailed while trying to eliminate waste generation from the material lifetime of the building. While most conventional construction methods are guided mostly by short-term economic benefits of the moment, green design seeks to strengthen environmental champions over time by concentrating their efforts on the long-term environmental stewardship. As a result, optimized energy consumption and sustainability is achieved only if green building systems with environment-friendly building materials and technologies are designed. The report puts a special focus on the green architecture complexity, pointing out its interdisciplinary character in the process. It analyses many different methods to achieve environmental sustainability, for example, it uses energy efficiency solutions and sustainable building methods. In addition to that, it deals with the way we can conserve natural resources. Furthermore, the article takes into account green architecture's participation in the resolution of the contemporary environmental problems that pose us serious threats like climate change and exhaustion of resources. With the help of green building systems, architects and designers can manufacture such places ready to resist the changing ecological environment and contribute to the betterment of ecological situation. Additionally the introduction of sustainable construction methods includes the variety of great humanization aspects such as improved indoor air quality, enhanced occupant comfort, and lowered operational costs. To summarize, this review suggests how we can adopt green architecture principles into the financial plan of the more popular and traditional builders. Through the emphasis of environmental coverage and adoption of environmentally friendlier modern techniques we can send a signal towards the direction of sustainable future for our societies.
Keywords: Building; Environment; Green architecture; Materials